Analisis Efektivitas Penyaluran Zakat Produktif (Studi pada BAZNAS Kota Surakarta) - Firdausa, Millenial Arkinto; Usnan, Usnan (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This research aims to determine the effectiveness of productive zakat that has been implemented by BAZNAS Surakarta City with analysis based on four aspect in the distribution of productive zakat funds, namely program socialization, accuracy of program targets, program monitoring or supervision and program objectives. This research used a qualitative approach with field research. Data collection techniques used are interviews, observation and documentation. The analysis technique in this research was the qualitative descriptive method started from the process of data collection, data reduction, presentation and conclusions. The results showed that the productive zakat program carried out by BAZNAS Surakarta City has not been effective. This finding was based on the four aspects studied, only one indicator was effective, namely target accuracy, while three aspects other still less effective. These findings indicate that the effectiveness of the productive zakat program by BAZNAS City of Surakarta still needs to be improved